2011
DOI: 10.1016/j.bone.2011.03.232
|View full text |Cite
|
Sign up to set email alerts
|

A program of microRNAs controls osteogenic lineage progression by targeting transcription factor Runx2

Abstract: Lineage progression in osteoblasts and chondrocytes is stringently controlled by the cell-fate-determining transcription factor Runx2. In this study, we directly addressed whether microRNAs (miRNAs) can control the osteogenic activity of Runx2 and affect osteoblast maturation. A panel of 11 Runx2-targeting miRNAs (miR-23a, miR-30c, miR-34c, miR-133a, miR-135a, miR-137, miR-204, miR-205, miR-217, miR-218, and miR-338) is expressed in a lineage-related pattern in mesenchymal cell types. During both osteogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 27 publications
8
85
0
Order By: Relevance
“…These findings corresponded well with the proposed role of miR-204, which regulates cellular transition in multiple cell types. 15,28,29 Recently, Runx2 has been reported to be closely associated with the osteoblast differentiation of VICs in aortic valve calcification. 30,31 Moreover, reactive oxygen species induces the expression of Runx2 through AKT signaling pathway, leading to activation of VICs toward an osteogenic-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…These findings corresponded well with the proposed role of miR-204, which regulates cellular transition in multiple cell types. 15,28,29 Recently, Runx2 has been reported to be closely associated with the osteoblast differentiation of VICs in aortic valve calcification. 30,31 Moreover, reactive oxygen species induces the expression of Runx2 through AKT signaling pathway, leading to activation of VICs toward an osteogenic-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the growth plates in transgenic mice and in chick limbs showed that Runx2 promoted chondrogenesis either by maintaining or by initiating early chondrocyte differentiation 34 . Furthermore, Runx2 regulated differentiation of MSCs as the target of miRNAs 48,49 . Moreover, C/EBPb could enhance the activity of Runx2 50 .…”
Section: Mrna Expression Of the Predicted Target Genes Before And Aftmentioning
confidence: 99%
“…Modifications of miR-125b-5p level have been involved in arterial calcification by smooth muscle cells 37 by regulating their transdifferentiation into osteoblast-like cells through the regulation of SP7 and RUNX2, 36 a marker of osteogenesis also found to be involved in arterial calcification. 38,39 MiR-204-5p also directly targets RUNX2. Five other target genes were found to be common between both miRNAs, including HAPLN1, an extracellular matrix protein interacting with proteoglycans and involved in cartilage development.…”
Section: Discussionmentioning
confidence: 98%